PKC Delta Activation Promotes Endoplasmic Reticulum Stress (ERS) and NLR Family Pyrin Domain-Containing 3 (NLRP3) Inflammasome Activation Subsequent to Asynuclein-Induced Microglial Activation: Involvement of Thioredoxin-Interacting Protein (TXNIP)/Thioredoxin (Trx) Redoxisome Pathway - Samidurai, Manikandan; Palanisamy, Bharathi N.; Bargues-Carot, Alejandra; Hepker, Monica; Kondru, Naveen; Manne, Sireesha; Zenitsky, Gary; Jin, Huajun; Anantharam, Vellareddy; Kanthasamy, Anumantha G.; Kanthasamy, Arthi (Frontiers in Aging Neuroscience, 2021)
A classical hallmark of Parkinson’s disease (PD) pathogenesis is the accumulation of misfolded alpha-synuclein (αSyn) within Lewy bodies and Lewy neurites, although its role in microglial dysfunction and resultant dopaminergic (DAergic) neurotoxicity is still elusive. Although protein kinase C delta (PKCδ) has been found to be activated in post mortem PD brains and experimental Parkinsonism and has been linked to endoplasmic reticulum stress (ERS)-induced apoptosis, the relationship between PKCδ activation, ERS and the reactive microglial activation state in the context of α-synucleinopathy is largely unknown. Herein, we show that oxidative stress, mitochondrial dysfunction, NLR family pyrin domain containing 3 (NLRP3) inflammasome activation, and PKCδ activation increased concomitantly with ERS markers, including the activating transcription factor 4 (ATF-4), serine/threonine-protein kinase/endoribonuclease inositol-requiring enzyme 1α (p-IRE1α), p-eukaryotic initiation factor 2 (eIF2α) as well as increased generation of neurotoxic cytokines, including IL-1β in aggregated αSynagg-stimulated primary microglia. Importantly, in mouse primary microglia-treated with αSynagg we observed increased expression of Thioredoxin-interacting protein (TXNIP), an endogenous inhibitor of the thioredoxin (Trx) pathway, a major antioxidant protein system. Additionally, αSynagg promoted interaction between NLRP3 and TXNIP in these cells. In vitro knockdown of PKCδ using siRNA reduced ERS and led to reduced expression of TXNIP and the NLRP3 activation response in αSynagg-stimulated mouse microglial cells (MMCs). Additionally, attenuation of mitochondrial reactive oxygen species (mitoROS) via mito-apocynin and amelioration of ERS via the eIF2α inhibitor salubrinal (SAL) reduced the induction of the ERS/TXNIP/NLRP3 signaling axis, suggesting that mitochondrial dysfunction and ERS may act in concert to promote the αSynagg-induced microglial activation response. Likewise, knockdown of TXNIP by siRNA attenuated the αSynagg-induced NLRP3 inflammasome activation response. Finally, unilateral injection of αSyn preformed fibrils (αSynPFF) into the striatum of wild-type mice induced a significant increase in the expression of nigral p-PKCδ, ERS markers, and upregulation of the TXNIP/NLRP3 inflammasome signaling axis prior to delayed loss of TH+ neurons. Together, our results suggest that inhibition of ERS and its downstream signaling mediators TXNIP and NLRP3 might represent novel therapeutic avenues for ameliorating microglia mediated neuroinflammation in PD and other synucleinopathies.